2018
DOI: 10.26434/chemrxiv.6353402.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Architectured Helically Coiled 3D Structures from Elastomeric Poly(butylene succinate)(PBS) Copolyester

Abstract: <div><div><div><p>Electrospinning is one of the most investigated methods used to produce polymeric fiber structures that mimic the morphology of native extracellular matrix. These structures have been extensively studied in the context of scaffolds for tissue regeneration. However, the compactness of materials obtained by traditional electrospinning, collected as two-dimensional non-woven scaffolds, can limit cell infiltration and tissue ingrowth. In addition, for applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There are several polyesters that fulfill some of the mentioned requirements for the construction of scaffold for tissue engineering applications: PEG, polycaprolactone (PCL), [ 237–239 ] PBS and PBSe based systems, [ 240–242 ] polyglycerol based polymers (synthesized from combination of glycerol and diacids), [ 243–245 ] among others, which have been proven to be ideal materials for their application in skin, nerve and cardiac tissue regeneration, besides others. However, in general all these polymers have been prepared via synthetic routes requiring of high reaction temperatures and the use of organic metals as catalyst, which may drag problems in their final applications.…”
Section: Bioapplicationsmentioning
confidence: 99%
“…There are several polyesters that fulfill some of the mentioned requirements for the construction of scaffold for tissue engineering applications: PEG, polycaprolactone (PCL), [ 237–239 ] PBS and PBSe based systems, [ 240–242 ] polyglycerol based polymers (synthesized from combination of glycerol and diacids), [ 243–245 ] among others, which have been proven to be ideal materials for their application in skin, nerve and cardiac tissue regeneration, besides others. However, in general all these polymers have been prepared via synthetic routes requiring of high reaction temperatures and the use of organic metals as catalyst, which may drag problems in their final applications.…”
Section: Bioapplicationsmentioning
confidence: 99%
“…In our previous studies, focusing on the idea of expanding the range of PBS copolymers, we found that the incorporation of poly (ethylene glycol) (PEG) into PBS-DLS copolymers increased their hydrophilicity, rubber-like elasticity and revealed excellent processability by fused filament fabrication (FFF) known also as 3D printing. Moreover, these new materials are also easily processed into nanofibers using electrospinning [13][14][15].…”
Section: Introductionmentioning
confidence: 99%